2019
DOI: 10.1177/1934578x19850354
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Health Benefits of Artemisia Species

Abstract: Artemisia L. is a genus of small herbs and shrubs found in northern temperate regions. It belongs to the important family Asteraceae, one of the most numerous plant groupings, which comprises about 1000 genera and over 20000 species. Artemisia has a broad spectrum of bioactivity, owing to the presence of several active ingredients or secondary metabolites, which work through various modes of action. It has widespread pharmacological activities and has been used as traditional medicine since ancient times as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 107 publications
4
145
0
2
Order By: Relevance
“…Moreover, A. vulgaris is consumed orally by local citizens as a traditional herbal for fever, headache, and stomachache. To the best of our knowledge, there has been no toxicity reported from citizens consuming A. vulgaris so far [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A. vulgaris is consumed orally by local citizens as a traditional herbal for fever, headache, and stomachache. To the best of our knowledge, there has been no toxicity reported from citizens consuming A. vulgaris so far [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these are two different species, it has been shown that within the Artemisia genus, many compounds are conserved; however, it is the small chemical nuances and profile that have a large effect on the biological activity (Abad et al, 2012). Medicinal plants species that are closely related may also produce similar or chemically similar compounds responsible for their biological activity (Nigam et al, 2019). This forms the basic definition for chemotaxonomy, which is the "closely related plants contain the same or similar chemical profiles" (Hao and Xiao, 2020).…”
Section: Potential Leads From Southern African Plantsmentioning
confidence: 99%
“…After administration, the artemisinins are rapidly absorbed, distributed and metabolized. Due to the emergence of resistance to oral artemisinin monotherapy (oAMT), it was replaced with artemisinin-based combination therapies (ACTs) (World Health Organization 2006, in which a fastacting artemisinin derivative is administered together with a slow-acting antimalarial drug of another class of antimalarials (Nigam et al 2019;Mohammadi et al 2020). ACTs are highly effective and efficacious globally and currently remain the recommended first-line treatment for uncomplicated malaria (World Health Organization 2010.…”
Section: Improving the Therapeutic Efficacy Of Artemisininmentioning
confidence: 99%